Drug Safety and Pharmacovigilance - Sharma, Samiksha; Sharma, Ashish; Shahid, M. K; Namdev, A; Khinchi, M. P.; S, Gaurav (Asian Journal of Pharmaceutical Research and Development, 2015)
Pharmacovigilance is related to improve patient care and safety in relation to the use of medicines. It is a public health activity focus on the identification, assessment and prevention of adverse reactions for marketed drugs and also focus on poly pharmacy, iatrogenesis, paradoxical reactions and serious adverse event. Adverse drug reaction may be in the process of pre-marketing or post-marketing surveillance are reported to the regulatory agency and concerned regulatory agency. During 1986 a formal adverse drug reaction (ADR) monitoring system was proposed in India However, nothing much happened until 1997, when India joined the World Health Organization (WHO) Adverse Drug Reaction Monitoring Programme based in Uppsala, Sweden. In India, pharmacovigilance has progressed from the situation as it was in past, an increase in drug safety concerns in recent years with some high profile drug withdrawals have led to raising the bar by various stakeholders more importantly by the regulatory authorities. A very broad definition of a drug "all chemicals other than food that affect living processes." If the affect helps the body, the drug is a medicine. However, if a drug causes a harmful effect on the body, the drug is a poison. The same chemical can be a medicine and a poison depending on conditions of use, dose and the person using it. The word pharmacovigilance has derived from the Greek word pharmacon means ‘drug’ and the Latin word vigilare means ‘to keep awake or alert, to keep watch. Pharmacovigilance as defined by the World Health Organisation (WHO) is ‘the science an activities relating to the detection, assessment, understanding and prevention of adverse effects or any other possible drug-related problems’. It involves evaluating information provided by health care providers, pharmaceutical companies and patients in order to understand the risks and benefits involved with a particular drug.